STUDI METODOLOGI HUKUM ISLAM: FIKIH PEMBAHARUAN DALAM PANDANGAN GAMAL AL-BANNA DAN RELEVANSINYA DENGAN PERKEMBANGAN FIKIH DI INDONESIA - Asyari, Khoirul Hadi (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2016)
This study is based on library research examines the discourse of fiqh reform in view of Gamal al-Banna. Gamal al-Banna is one of the younger brothers of Hasan al-Banna. This study has  some questions: first, what is Gamal al-Banna’s opinion; second, how social and political biography that covers the life of Gamal al-Banna; third, how their relevance to the development of jurisprudence in Indonesia. By the qualitative research methods, analytical content, historical approach and content analysis are used to investigate the books related in gaining datas of Gamal al-Banna’s thought, while historical approach try to investigate how scope and biographies are in the neighborhood of Gamal al-Banna. The results of this study are: first, Gamal al-Banna reforms fiqh more moderate than his brother Hassan al-Banna; secondly, to know Gamal al-Banna's life biography; and third, determine its relevance to the development of Fiqh reform in Indonesia. Kata Kunci : Fikih, Pembaharuan, Gamal, Relevansi